The New Orientation of Health Regime in Costa Rica: An Approach to the Institutional Crisis Context of the Social Insurance After The 75th Anniversary of the Social Warrants Promulgation - Araya Vargas, Andrés (2019)
Since the discussion of the health politics and its interaction with the neoliberal market demands, the projection of the social insurance is performed in the medicine area in Costa Rica after celebrating its 75th Social Warranties promulgation anniversary where the Caja Costarricense del Seguro Social is exposed as an institution without lucrative purposes that looks out for ideologies related to social welfare. In the analysis, the logic of the social welfare and the transfiguration according to their officials and users is discussed. As the same way, a social critic about this medical institution society appropriate discursive and the economic valuations originated from it.